Reliability simulation analysis and optimization design of the electronic control proceeding controller - MA Fangyun; SUN Xi; LEI Huajin (Hangkong gongcheng jinzhan)
With the increasing reliability requirements of electronic products, the use of failure physics methods to identify potential weak points in product design has attracted much attention. In this paper, the theory of failure physics and reliability simulation analysis method are used to analyze the reliability of electronic controller. By establishing a digital prototype model of electronic controller, the corresponding stress analysis and fault prediction are conducted to evaluate the mean time to first failure（MTTFF）reliability index of the electronic controller, and optimize the design based on the weak links found in simulation results. It is indicated that the difference between the reliability results and the theoretical calculation results are not significant, and can be used as a basis for evaluating the reliability indicators of models, reducing the cycle and cost of using physical prototypes for reliability testing. At the same time, the optimization and improvement have significantly improved the reliability design of the electronic controller, laying a theoretical foundation for subsequent model reliability evaluation and design.